Uji variasi temperatur dan campuran bahan bakar terhadap karakteristik spray - Rafdi, M.H.A.; Ilminnafik, N.; Djumhariyanto, D.; Setyawan, D.L.; Sutjahjono, H.; Sanata, A.; Hardiatama, I. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2022)
The use of biodiesel fuel has a very high viscosity and density compared to diesel oil, this makes diesel engine performance less than optimal. With the addition of gasoline to biodiesel, it will reduce the viscosity and density of biodiesel and have a lower flash point. And also the fuel heating process aims to reduce the level of viscosity and density of the fuel so that it is the same as diesel oil. This study aims to know the spray characteristics of fuel B0 (100% diesel oil), B30 (30% biodiesel and 70% diesel oil) and B30G5 (95%B30 and 5% diesel oil) with temperature variations 60ºC, 80ºC, and 100ºC on injection pressure of 17 MPa. The results of the tests that have been carried out that the increase in temperature of the fuel and variations in injection pressure will affect the value of the spray tip penetration, and the spray area. The result of the spray characteristic test that produces a good value is B0 fuel (100% diesel) but the closest to the B0 fuel value is B30G5.